Basic discrete structures - Din, Roshidi; Kamaruddin, Siti Sakira; Amphawan, Angela; Omar, Mohd Nizam (Universiti Utara Malaysia Press, 2015)
Digital technology has pervaded almost all spheres of life.Due to the importance of discrete information in our increasingly digital world, familiarity with the underlying principles, concepts and operations on discrete information is inevitable.This book is intended as a basic course for introducing students to abstract mathematical structures to represent discrete information and relationships between them.These discrete structures include sets, sequences, permutations, combinations, functions, trees and finite-state machines which are predominantly used in computer science and data networking, and extended to fields which involve the organization, computation or optimization of objects from a large data set such as to botany, geography, chemistry, genetics, zoology, finance and linguistics. While the book is light, a good balance is struck between the teaching of basic concepts and the exposure to practical applications to demonstrate the relevance and practicality of discrete structures in modeling and solving real-world problems.